Detektor Dini Kebakaran Multisensor Terintegrasi Android Menggunakan Komunikasi Bluetooth - Maulana Hasan; Adnan Rafi Al Tahtawi (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This research aims to design fire early warning system using Arduino and Android with Bluetooth communication. The system is constructed using three sensors which are KY-026 flame detector, DS18B20 temperature sensor, and MQ-07 gas sensor. The communication used HC-05 Bluetooth module to send sensor data from Arduino to Android. Testing results show that Arduino through Bluetooth communication able to send sensor data to Android within range of 20 cm with no obstacle condition and range of 10 cm if there exists the obstacle. The system will send ‘normal’ status to Android when fulfilled this conditions: flame sensor value less than 200, temperatures less than 30°C, and gas levels less than 300 ppm. There are seven other conditions that contain ‘warning’ and ‘danger’ data if those condition above not fulfilled.